Isolation and Characterization of Adenovirus Messenger Ribonucleic Acid in Productive Infection - Lindberg, Uno (1972)
Messenger ribonucleic acid (mRNA) from cells productively infected with adenovirus type 2 was isolated by affinity chromatography on polyuridylic acid [poly (U)] bound to Sepharose. At least 90% of the polyadenylic acid [poly (A)]-containing polysomal mRNA was retained by the poly (U) Sepharose and thus separated from more than 95% of the ribosomal RNA and transfer RNA. In these experiments, 65% of the early (3 to 5 hr postinfection) and 85% of the late (14 to 16 hr postinfection) virus-specific RNA was retained by the poly (U) Sepharose. Early in the infection 18%, and late in the infection more than 95%, of the poly (A)-containing fraction, eluted from the poly (U) Sepharose with 90% formamide, was adenovirus-specific, as shown by exhaustive hybridization. Different patterns, containing several distinct species of viral mRNA, were detected early and late in the infectious cycle. No distinct viral mRNA lacking poly (A) was discovered.